Gut pathobiont enrichment observed in a population predisposed to dementia, type 2 diabetics of Mexican descent living in South Texas - Matz, Lisa M.; Shah, Nisarg S.; Porterfield, Laura; Stuyck, Olivia M.; Jochum, Michael D.; Kayed, Rakez; Taglialatela, Giulio; Urban, Randall J.; Buffington, Shelly A. (Frontiers in Microbiomes, 2024)
Type 2 diabetes (T2D) is a common forerunner of neurodegeneration and accompanying dementia, including Alzheimer’s Disease (AD), yet the mechanisms underlying this comorbidity remain unresolved. Individuals of Mexican descent living in South Texas have increased prevalence of comorbid T2D and early onset AD, despite low incidence of the APOE-ε4 risk variant among the population and an absence of a similar predisposition among relatives residing in Mexico – suggesting a role for environmental factors in coincident T2D and AD susceptibility. We therefore sought to test if differences in gut community structure could be observed in this population prior to any AD diagnosis. Here, in a small clinical trial (ClinicalTrials.gov Identifier NCT04602650), we report evidence for altered gut microbial ecology among subjects of Mexican descent living in South Texas with T2D (sT2D) compared to healthy controls without T2D (HC), despite no differences in expressed dietary preferences. We performed metataxonomic 16S rRNA gene amplicon sequencing of study participant stool samples. Although no significant decrease in microbial alpha diversity was observed between sT2D gut communities versus those of HC, body mass index was identified as a driver of gut community structure. Intriguingly, we observed a significant negative association of Faecalibacterium and Lachnospiraceae with T2D and an increase in the abundance of pathobionts Escherichia-Shigella, Enterobacter, and the erysipelotrichial species Clostridia innocuum among sT2D gut microbiota, as well as differentially abundant gene and metabolic pathways. Future large-scale, longitudinal sequencing efforts of the gut microbiome of individuals with T2D who go on to develop AD might identify key actors among “disease state” microbiota that contribute to increased susceptibility to comorbid dementia. Finally, we identified candidate microbiome-targeted approaches for the treatment of T2D.